Diagnóstico situacional sobre la integración de la investigación de grado y posgrado en la carrera de Educación Básica de la Universidad Técnica de Cotopaxi. - Cambo Yugsi, Luis Jaime (2018)
Research is considered as a key piece for the construction of knowledge, professional training and the resolution of the concrete problems of society. This research project, start of the problem of the nonexistent articulation of undergraduate and postgraduate research in the basic education career at Technical University of Cotopaxi, where the low development of investigative skills has been identified in the students of the mentioned career mentioned, as well as the negative perspective of teachers and students against the contribution of research as part of the training processes, so this educational function is considered as an activity which fulfillment has as its ultimate goal the obtaining of a qualification without recognizing the contribution of research in vocational training, on the other hand it is also identified that there is currently no possibility for students in the basic education career to continue with the research and training processes in the fourth level, opting for a masters, specialization or phd, It makes possible to take its theoretical investigations to the empirical professional field and to establish concrete solutions to the research problems. The established objective was to diagnose the integration of undergraduate and postgraduate research in the basic education career Technical University of Cotopaxi, for which a methodology framed in the positivist paradigm and the qualitative approach through the techniques was applied, observation and the instruments of observation cards or checklists, focused on describing the characteristics of the research carried out in undergraduate and postgraduate training in the Basic Education career, as well as scientific production during the period 2015-2018. It is essential to mention that the articulation of the function of undergraduate research with a postgraduate degree in the educational field plays a very important role, in the cognitive development of human beings, especially students, since in the university is where the student incorporates all the knowledge that will help them perform efficiently in the professional field. The results obtained have been able to identify that the research in the basic education career has been developed mostly in the upper levels of undergraduate, as a mean to sustain the degree, while at the graduate level there has been a poor level of research between the years 2015-2018, at present there are no fourth level programs that are offered for the basic education career.